Contribution of wide field angiography to diabetic macular edema - Maamouri, R.; Bouraoui, R.; Kort, F.; Falfoul, Y.; El Matri, K.; El Matri, L. (Acta ophthalmologica (Oxford, England), 2016)
Purpose To evaluate diabetic macular edema in non proliferative diabetic retinopathy (NPDR) using a wide field fluorescein angiography. Methods In a retrospective study, consecutive wide‐field angiographs using the Heidelberg Retina Angiograph 2 with a contact lens system Staurenghi and SD‐OCT were performed in diabetic patients with non proliferative diabetic retinopathy. Results A total of 71 eyes in 39 diabetic, average age was 58 years (SD 12). Most of the patients had type 2 diabetes mellitus (92%) and average duration since diabetes diagnosis was 10 years. Mean HA1c was 7.4%. Distribution of NPDR severity was: mild NPDR in 6% of eyes, moderate NPDR in 21% and severe NPDR in 73%. Macular edema was found in 53%. A thicker retina was observed in eyes with peripheral non perfusion (353 vs. 254 μm p = 0.006). Retinal non perfusion was associated with macular edema (97 vs. 76%, p = 0.01) and poor visual acuity (p < 0.001). Conclusions Diabetic macular edema seems to be strongly associated with peripheral retinal non perfusion. So treatment and management of diabetic macular edema may be reconsidered using either a targeted laser treatment in the area of retinal non perfusion or anti‐VEGF intravitreal injection.